The microRNA-183/96/182 Cluster is Essential for Stereociliary Bundle Formation and Function of Cochlear Sensory Hair Cells. Issue 1 (December 2018) - Geng, Ruishuang; Furness, David; Muraleedharan, Chithra; Zhang, Jinsheng; Dabdoub, Alain; Lin, Vincent; Xu, Shunbin
Abstract The microRNA (miR)-183/96/182 cluster plays important roles in the development and functions of sensory organs, including the inner ear. Point-mutations in the seed sequence of miR-96 result in non-syndromic hearing loss in both mice and humans. However, the lack of a functionally null mutant has hampered the evaluation of the cluster's physiological functions. Here we have characterized a loss-of-function mutant mouse model (miR-183CGT/GT ), in which the miR-183/96/182 cluster gene is inactivated by a gene-trap (GT) construct. The homozygous mutant mice show profound congenital hearing loss with severe defects in cochlear hair cell (HC) maturation, alignment, hair bundle formation and the checkboard-like pattern of the cochlear sensory epithelia. The stereociliary bundles retain an immature appearance throughout the cochlea at postnatal day (P) 3 and degenerate soon after. The organ of Corti of mutant newborn mice has no functional mechanoelectrical transduction. Several predicted target genes of the miR-183/96/182 cluster that are known to play important roles in HC development and function, includingClic5, Rdx, Ezr, Rac1, Myo1c, Pvrl 3 andSox2, are upregulated in the cochlea. These results suggest that the miR-183/96/182 cluster is essential for stereociliary bundle formation, morphogenesis and function of the cochlear HCs.